The Enzyme Immobilization: Carriers and immobilization methods - Milica Spasojevic; Olivera Prodanović; Pantic Nevena; Nikolina Popovic; Ana Marija Balaz; Radivoje Prodanovic (Journal of Engineering & Processing Management, 2019)
Strategies based on the enzyme application are increasingly replacing the conventional chemical procedures because of their efficiency, quicker performance and environmental protection. However, natural enzymes can rarely be used in industry since their beneficial features can not endure the industrial conditions. Additional drawbacks of natural enzymes are their inhibition by reaction products and difficulty to be removed from the reaction mixture. The most promising technique to substantially improve the enzyme properties, such as activity, pH, thermal and organic-solvent stability, reusability and storage stability, in non-natural environments is by the enzyme immobilization. In this review we summarized different techniques used to immobilize enzymes to inert carriers. A wide variety of materials of both the organic and inorganic origin was used as carriers for the enzyme immobilization. We also summarized a class of new materials where the enzyme performance was enhanced by combining different classical materials and shaping in specific forms.
Keywords: enzymes; macroporous; carriers; hydrogels